Biology learning innovation in the water pollution sub material based on sustainable development goals (SDGs) using the problem-based learning - Nabila Nabila; Marisa Christina Tapilouw; Sucahyo Sucahyo (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2023)
Sustainable Development Goals (SDGs) are a global issue initiated by the United Nations. One goal of SDGs is "clean water and sanitation" regarding water pollution issues. This research aims to develop learning media on the material "Water pollution" in the form of 360° Videos and water purification tools to introduce Sustainable Development Goals (SDGs), determine the effectiveness of learning innovations in improving learning outcomes, and also determine the feasibility of 360° Video learning media and water purification tools. This research is developing learning media with 4D models (Define, Design, Development, and Disseminate). The media developed are 360° Video and water purification devices. The value of 360° video validation is 93.3%, and the water purification device is 91.25% with the very valid category. The learning media developed was able to improve learning outcomes with an N-Gain value of 0.508 in the medium category. The value of effectiveness is 80.66% with the effective category. 360° Videos and water purification tools improved student learning outcomes, SDGS understanding of the clean water and sanitation goals, and student enthusiasm.Abstrak Sustainable Development Goals (SDGs)  merupakan isu global yang diinisiasi oleh PBB. Salah satu tujuan SDGs yaitu Clean water and Sanitation, berdasarkan masalah pencemaran air.  Tujuan penelitian ini yaitu untuk mengembangkan media pembelajaran pada materi “pencemaran air” dalam bentuk Video 360° dan alat penjernihan air untuk memperkenalkan Sustainable Development Goals (SDGs), dan menentukan efektivitas inovasi pembelajaran dan kelayakan Video 360° dan alat penjernihan air. Penelitian ini merupakan pengembangan media pembelajaran dengan model 4D (Define, Design, Development, dan Disseminate). Media yang dikembangkan yaitu Video 360° dan alat penjernihan air. Hasil validasi video 360 yaitu 93,3% dan alat penjernihan air yaitu 91,25% dengan kategori sangat valid. Media pembelajaran yang dikembangkan mampu meningkatkan hasil belajar dengan nilai N-Gain sebesar 0,508 pada kategori sedang.  Pada aspek efektivitas, mendpatkan nilai 80,66% dengan kategori efektif.  Video 360° dan alat penjernihan air mampu meningkatkan hasil belajar siswa, pemahaman SDGs Clean water and Sanitation dan antusiasme siswa.